Blood Pressure Management After Endovascular Thrombectomy - Peng, Teng J.; Ortega-Gutiérrez, Santiago; de Havenon, Adam; Petersen, Nils H. (Frontiers in Neurology, 2021)
Endovascular thrombectomy (EVT) has changed the landscape of acute stroke therapy and has become the standard of care for selected patients presenting with anterior circulation large-vessel occlusion (LVO) stroke. Despite successful reperfusion, many patients with LVO stroke do not regain functional independence. Particularly, patients presenting with extremes of blood pressure (BP) or hemodynamic variability are found to have a worse clinical recovery, suggesting blood pressure optimization as a potential neuroprotective strategy. Current guidelines acknowledge the lack of randomized trials to evaluate the optimal hemodynamic management during the immediate post-stroke period. Following reperfusion, lower blood pressure targets may be warranted to prevent reperfusion injury and promote penumbral recovery, but adequate BP targets adjusted to individual patient factors such as degree of reperfusion, infarct size, and overall hemodynamic status remain undefined. This narrative review outlines the physiological mechanisms of BP control after EVT and summarizes key observational studies and clinical trials evaluating post-EVT BP targets. It also discusses novel treatment strategies and areas of future research that could aid in the determination of the optimal post-EVT blood pressure.